Coexistence of Pituitary Adenoma and Primary Pituitary Lymphoma: A Case Report and Review of the Literature - Ren, Shangjun; Lu, Qingyang; Xiao, Yilei; Zhang, Yiming; Zhang, Lianqun; Li, Bin; Li, Mengyou (Frontiers in Surgery, 2022)
In the pituitary sella, the coexistence of pituitary adenoma and primary pituitary lymphoma is exceedingly rare. Thus far, only six cases have been reported. Here, we present the seventh case of coexisting pituitary adenoma and primary pituitary lymphoma, which was difficult to differentiate from other sellar tumors. To our knowledge, this is the first case of the prolactin subtype of the pituitary adenoma in literature. We have also systematically reviewed the literature and summarized the characteristics of coexisting pituitary adenoma and lymphoma. We believe this report provides a new clinical reference for the diagnosis and treatment of collision tumors of pituitary adenoma and lymphoma.